Carotid stiffness change over the cardiac cycle by ultrafast ultrasound imaging in healthy volunteers and vascular Ehlers–Danlos syndrome. Issue 9 (September 2015) - Mirault, Tristan; Pernot, Mathieu; Frank, Michael; Couade, Mathieu; Niarra, Ralph; Azizi, Michel; Emmerich, Joseph; Jeunemaître, Xavier; Fink, Mathias; Tanter, Mickaël; Messas, Emmanuel
Abstract : Objectives: Arterial stiffness is related to age and collagen properties of the arterial wall and can be indirectly evaluated by the pulse wave velocity (PWV). Ultrafast ultrasound imaging, a unique ultrahigh frame rate technique (>10 000 images/s), recently emerged enabling direct measurement of carotid PWV and its variation over the cardiac cycle. Our goal was to characterize the carotid diastolic–systolic arterial stiffening using ultrafast ultrasound imaging in healthy individuals and in vascular Ehlers–Danlos syndrome (vEDS), in which collagen type III is defectuous. Methods: Ultrafast ultrasound imaging was performed on common carotids of 102 healthy individuals and 37 consecutive patients with vEDS. Results are mean ± standard deviation. Results: Carotid ultrafast ultrasound imaging PWV in healthy individuals was 5.6 ± 1.2 in early systole and 7.3 ± 2.0 m/s in end systole, and correlated with age ( r = 0.48; P < 0.0001 and r = 0.68; P < 0.0001, respectively). Difference between early and end-systole PWV increased with age independently of blood pressure ( r = 0.54; P < 0.0001). In patients with vEDS, ultrafast ultrasound imaging PWV was 6.0 ± 1.5 in early systole and 6.7 ± 1.5 m/s in end systole. Carotid stiffness change over the cardiac cycle was lower than in healthy people (0.021 vs. 0.057 m/s per mmHg; P = 0.0035). Conclusion: Ultrafast ultrasound imaging can evaluate carotid PWV and its variation over the cardiac cycle. This allowed to demonstrate the age-induced increase of the arterial diastolic–systolic stiffening in healthy people and a lower stiffening in vEDS, both characterized by arterial complications. We believe that this easy-to-use technique could offer the opportunity to go beyond the diastolic PWV to better characterize arterial stiffness change with age or other collagen alterations. Abstract : Supplemental Digital Content is available in the text